PENGARUH PRODUCT DIVERSITY, PERCEIVED PRICE DAN STORE ATMOSPHERE TEHADAP KEPUTUSAN PEMBELIAN DALAM PERSPEKTIF BISNIS ISLAM: Studi pada konsumen Dikromoshop, Sukarame Bandar Lampung - Resa, Tja Alta; Devi, Yulistia (CV ODIS, 2024)
The purpose of this research is to determine the influence of Product Diversity, Perceived Price and Store Atmosphere on Purchasing Decisions from an Islamic Business Perspective (Study of Dikromoshop Consumers, Sukarame Bandar Lampung). This research uses quantitative/methods. The data collection method was carried out by distributing questionnaires to Kromoshop consumers via offline Google Form. The sample in this research was 100 Dikromoshop consumers in Sukarame, Bandar Lampung. The sampling technique uses random sampling technique, the analysis process uses SPSS 20. The research results show that product diversity has a significant effect on purchasing decisions. The perceived price variable also has a significant influence on purchasing decisions. The store atmosphere variable also has a significant effect on purchasing decisions. Product diversity, perceived price and store atmosphere simultaneously have a significant influence on purchasing decisions.